Implication of Environmental Management System and Environmental Performance on Financial Performance of Entities with Foreign Ownership as Moderator - Anggara, Berwin; Safitri, Vera Apri Dina; Naz, Isbahna (Universitas Muhammadiyah Magelang, 2021)
This research aims to examine the determination of the Environmental Management System (EMS) and environmental performance on the company's financial performance as moderated by foreign ownership in the stock structure of manufacturing companies listed on the Indonesia Stock Exchange. This research uses a quantitative method by analyzing 27 manufacturing companies listed on the IDX through purposive sampling-based sample selection, then data analysis using the moderated regression analysis method. The results showed that foreign ownership could not moderate the effect of EMS proxied by ISO 14001 certification on the financial performance of the entity proxied by ROA, but on the other hand, the structure of foreign ownership shares could positively and significantly moderate the effect of environmental performance proxied by PROPER KLHK. on the entity's financial performance. Meanwhile, if tested directly, neither EMS nor environmental performance has an effect on the company's financial performance.